2019
DOI: 10.3889/oamjms.2019.120
|View full text |Cite
|
Sign up to set email alerts
|

Successful Endovascular Treatment of a Giant Hepatic Artery Aneurysm with Dual Layer Stents Placement as Flow-Diverting Option: Case Report

Abstract: BACKGROUND: Visceral artery aneurysms are rare conditions. The incidence of hepatic artery aneurysm (HAA) accounts for approximately 20% of all splanchnic aneurysms. HAA can become a life-threatening situation because there is a great risk of rupture when it grows more than 2 cm in diameter. CASE PRESENTATION: In this article, we describe a case of a 54-year-old female patient with large hepatic artery aneurysm which was incidentally founded. From symptoms, she had abdominal discomfort slightly worsening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Aleksandar et al reported a case of a giant hepatic artery aneurysm treated with dual layer stent placement as flowdiverting option. The hypothesis of preserving side branches that arise from the aneurysm or close to it may be an 3 BioMed Research International additional potential advantage of dual layer stents over traditional stent grafts [15].…”
Section: Discussionmentioning
confidence: 99%
“…Aleksandar et al reported a case of a giant hepatic artery aneurysm treated with dual layer stent placement as flowdiverting option. The hypothesis of preserving side branches that arise from the aneurysm or close to it may be an 3 BioMed Research International additional potential advantage of dual layer stents over traditional stent grafts [15].…”
Section: Discussionmentioning
confidence: 99%
“…HAAs account for 20% of all visceral aneurysms. With a poorly understood natural history, HAA is difficult to diagnose clinically [ 10 , 11 ]. The choice of treatment depends on the clinical presentation, associated risk factors, and general patient status, and vascular comorbidities should be considered, particularly in patients with arterial aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…In one meta-analysis evaluating 80 cases, 359 out of 2845 visceral aneurysms were hepatic (12%), with an incidence of 0.01 to 0.2% [3,6]. HAAs are approximately 20% of splanchnic aneurysms and are at risk of rupturing when diameter exceeds 2 cm [10][11] There have not been enough cases to determine the best way to repair them -i.e. open vs. endovascularly.…”
Section: Discussionmentioning
confidence: 99%
“…Definitive measures for intact or ruptured HAA, given the rarity of the disease, are not standardized [1,6,10]. However, it is reasonable to treat this pathology similar to an intact or ruptured aortic aneursym -decrease the shearing forces with beta-blockers.…”
Section: Discussionmentioning
confidence: 99%